KREATIVITAS ANAK USIA DINI BERDASAKAN ALIRAN PROGRESIVISME - Tita Pertama Wati; Maemunah Maemunah (Pendidikan Guru PAUD, FKIP, Univ Muhammadiyah Tasikmalaya, 2021)
Abstract : In this research, the writer aims to be able to know what creativity is, the importance of cultivating creativity, and the relevance of creativity according to the flow of progressivism. As we know that early childhood is usually called the golden age, which means the golden age. Cognitive, fine-gross motor, social-emotional, language, religious-moral, and artistic aspects are various aspects of early childhood. Therefore, educators and parents should understand how important creativity is for their future survival. It is an absolute obligation to introduce various kinds of activities that foster children's creativity so that they develop properly and correctly based on the child's age stage. Today there is still an understanding of parents, communities or teachers who have not optimally understood the benefits of the importance of creativity for early childhood for the next child's life, and the author tries to explain the relationship between early childhood creativity based on the flow of progressivism. Thus, the development of creativity in early childhood is expected to be able to optimize understanding and knowledge about the importance of creativity for children. The important role of creativity includes creativity being able to realize self-actualization, and it is a reflection of creative thinking, creativity allows humans to improve the quality of life and is beneficial for the social environment. The authors use the type of library research (library research). Early childhood creativity based on the flow of progressivism is strengthened by related theories so that it is very educational for readers to implement in everyday life in educating children. Keywords: Creativity Development, Early Childhood, Progresivisme.